The Influence of Place Attachment on Pro-environmental Behaviour Intentions Mediated by Place Satisfaction in Taman Menteng, Jakarta - Aristawidya Bandiani; Wara Indira Rukmi; Wisnu Sasongko (Dinasti Publisher, 2024)
This research examines the relationship between place attachment and pro-environmental behavioral intentions which is mediated by the place satisfaction variable. Quantitative analysis is carried out using statistical methods (descriptive, Likert, SEM-PLS) to prove the hypothesis that has been established. Observations were carried out to assess the behavior of park users using behavior mapping analysis as well as assessing the quality of the park based on the Project for Public Spaces. This research has succeeded in collecting data from 148 respondents, all of whom have visited Menteng Park, Central Jakarta. The demographic profile of respondents shows the dominance of female visitors (58.1%) and the majority aged between 25 to 34 years (37.9%). Most respondents came from the Jakarta area (74.3%), indicating that Menteng Park is visited more by local residents. In terms of education, respondents were dominated by undergraduate (41.9%) and high school (39.9%). Analysis of respondents' answers regarding place attachment shows a positive relationship where the result reflects the success of Menteng Park in providing adequate facilities for activities enjoyed by visitors. The results of hypothesis testing show that there is a positive relationship between place attachment, place satisfaction, and pro-environmental behavior intentions in Taman Menteng, Central Jakarta.